Patent Exhaustion and International Trade Regulation (Brill, 2023)
This book dives into the legal and economic rationale of patent exhaustion, studying its evolution from the beginning in Germany, UK and USA, to Japan and 10 developing countries. The author also analyses exhaustion under TRIPS, GATT, GATS and major regional agreements, including the EU, before assessing the interface of patent exhaustion with competition policy. The book also addresses public policy concerns of Least developed and developing countries linked to their IPR challenges as IP users. It concludes that an appropriate exhaustion mode under relevant legal measures would protect patents while also restraining patents to become non-tariff barriers.